2016
DOI: 10.5038/1827-806x.45.3.1983
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal temperature variations controlling cave ventilation processes in Cueva Larga, Puerto Rico

Abstract: Abstract:Two years of cave monitoring investigate ventilation processes in Cueva Larga, a tropical cave in Puerto Rico. The cave is 1,440 m long with a large main passage (about 120,000 m 3 ). Cave air pCO 2 in the main passage varies seasonally, between 600 ppm in winter and 1,800 ppm in summer. The seasonal variability in cave pCO 2 permits the estimation of a cave air exchange time of 36 ± 5 days and a winter ventilation rate of 3,300 ± 1,000 m 3 /day for the main cave passage. Calculations of virtual tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Environmental monitoring of Larga cave commenced in 2012. Previous studies have identified seasonal cave ventilation changes in this cave (Vieten et al, ), and preliminary data from two drip sites imply that they are fed by seepage water which might take years to travel from the surface to the cave (Vieten et al, ). Here monthly observations from six drip sites, sampled between 2012 and 2015, are presented.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Environmental monitoring of Larga cave commenced in 2012. Previous studies have identified seasonal cave ventilation changes in this cave (Vieten et al, ), and preliminary data from two drip sites imply that they are fed by seepage water which might take years to travel from the surface to the cave (Vieten et al, ). Here monthly observations from six drip sites, sampled between 2012 and 2015, are presented.…”
Section: Introductionmentioning
confidence: 87%
“…Glass slides deposited below these drip sites show evidence of active calcite precipitation. The drip sites are located in the distant part of the cave, where the air temperature is constant and relative humidity is near 100% (Vieten et al, ). These are preferred conditions to retrieve speleothem climate records (Fairchild & Baker, ).…”
Section: Methodsmentioning
confidence: 99%
“…The virtual temperature calculation included CO 2 effects which are not measured systematically in the present study. Nevertheless, it is not clear if the CO 2 concentration (or P CO 2 ) contributes to the driving force (see the opposite analysis of Vieten et al (2016) and Peyraube et al (2017)). A more precise discussion about the CO 2 effect in our case is presented at the next subsection.…”
Section: Annual Inversionsmentioning
confidence: 88%
“…Many others authors introduce the virtual temperature (Sánchez-Cañete et al 2013;Faimon et al 2012;Vieten et al 2016) instead of the Rayleigh number to estimate the driving force. The virtual temperature calculation included CO 2 effects which are not measured systematically in the present study.…”
Section: Annual Inversionsmentioning
confidence: 99%
“…Caves are a result of karstification and they are specific parts of vadose zone where external atmosphere air mixes with vadose zone air (Baldini et al, 2006). Depending on numerous processes and conditions (e.g., temperature, pressure gradient, wind direction, cave geometry), the cave air CO 2 undergoes variations throughout the year, though normally is more concentrated than the open atmosphere level (Kowalczk & Froelich, 2010;Fairchild & Baker, 2012;Gregorič et al, 2013;Pflitsch & Piasecki, 2003;Geiger, 1961;Vieten et al, 2016b;Baldini, 2010;Benavente et al, 2010;Bourges et al, 2014;Breecker et al, 2012;Fernández-Cortés et al, 2011, 2015Mattey et al, 2016, among others).…”
Section: Introductionmentioning
confidence: 99%